DENGRAPH: A Density-based Community Detection Algorithm - Falkowski, Tanja; Barth, Anja; Spiliopoulou, Myra (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
Detecting densely connected subgroups in graphs such as communities in social networks is of interest in many research fields. Several methods have been developed to find communities but most of them have a high time complexity and are thus not applicable for large networks. Inspired by the clustering algorithm incremental DBSCAN we propose a density-based graph clustering algorithm DENGRAPH that is designed to deal with large dynamic datasets with noise and present first experimental results.